INVENTING OUR SUCCESSORS: RATIONALIZING INNOVATIONS IN TECHNOLOGY AND THE TRAJECTORY OF HUMAN MISANTHROPIC BEHAVIOUR - Lancelot, Jonathan (Cyberpolitik Journal, 2022)
This paper is designed to explicate the parallels of technological innovation and human misanthropic behavior. Humanity's continuous and historical predilection for war and conflict has been augmented by human-created technologies like artificial intelligence, automation, robotics, and software platforms. The ontological question is asked, does technology have the ability to take the initiative to use human beings, altering the human-machine relationship as machines to develop the misanthropic behaviors on the behalf of its human inventors, quickening the possibility of megadeath by nuclear war, pandemic, or total extinction? The problem is first separated into parts by the process of philosophical deconstruction, then a set of proposed solutions are presented.